2023
DOI: 10.1111/1759-7714.14981
|View full text |Cite
|
Sign up to set email alerts
|

High density and proximity of CD8+T cells to tumor cells are correlated with better response to nivolumab treatment in metastatic pleural mesothelioma

Abstract: Background The efficacy of immune checkpoint inhibitors (ICIs) in pleural mesothelioma has recently been established. The response to ICIs can be predicted by quantitative analysis of cells and their spatial distribution in the tumor microenvironment (TME). However, the detailed composition of the TME in pleural mesothelioma has not been reported. We evaluated the association between the TME and response to ICIs in this cancer. Methods A retrospective analysis of 22 pleural mesothelioma patients treated with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Compared to the nonresponse group, CD8 + T cells in the response group were more clustered and located closer to tumor cells, whereas regulatory T cells were located further from tumor cells. 47 However, in a study of esophageal squamous cell carcinoma patients treated with first-line F I G U R E 5 TIL distribution pattern in the tumor and stromal regions. Except for PD-1-positive T cells, the densities of other detected TILs in the stroma region were significantly higher than those in the tumor region (paired Wilcox test, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the nonresponse group, CD8 + T cells in the response group were more clustered and located closer to tumor cells, whereas regulatory T cells were located further from tumor cells. 47 However, in a study of esophageal squamous cell carcinoma patients treated with first-line F I G U R E 5 TIL distribution pattern in the tumor and stromal regions. Except for PD-1-positive T cells, the densities of other detected TILs in the stroma region were significantly higher than those in the tumor region (paired Wilcox test, p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging evidence has indicated that the spatial distribution of TILs could precisely reflect the interactions between immune and tumor cells, but the detailed distribution pattern for favorable response and prognosis is unclear. [43][44][45][46][47] In a retrospective study of pleural mesothelioma patients treated with nivolumab, total T-cell infiltration in the tumor nest was similar to that in the extratumoral area. Compared to the nonresponse group, CD8 + T cells in the response group were more clustered and located closer to tumor cells, whereas regulatory T cells were located further from tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relative abundance of T cells in these tumors, there have been only very modest responses to T cell-centric therapies alone such as CheckMate 743 study (NCT02899299) for MPM and MPeM. Indeed, Yin et al recently showed high density and spatial proximity of CD8 + T cells to tumor cells were associated with better response to nivolumab, whereas the proximity of regulatory T cells to tumor cells was associated with worse response 19 . Our findings suggest that the distinct landscape of the TIME could be a potential predictor of the efficacy of immune checkpoint inhibitors (ICIs) in MPM.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that the distance between immune cells and tumour cells may directly represent the immune system's potency against cancers or, alternatively, the ability of tumour cells to modify immune cells. Yin et al [25] reported that the closer cytotoxic cell cluster was significantly correlated with better Progression-free survival (p = 0.038). Our results reveal that while there were trends for intratumoural T cell infiltration and reduced recurrence risk across all the CRC cohorts, they were not significant.…”
Section: Two Distinct Clusters Within Stage III Colorectal Cancer Tum...mentioning
confidence: 99%